2022
DOI: 10.1177/14680874221107141
|View full text |Cite
|
Sign up to set email alerts
|

The effects of variable excess air ratio and ignition timing on the performance and exhaust emissions in a direct injection Hydrogen-CNG fueled engine

Abstract: This study investigates a direct injection (DI) engine fueled with compressed natural gas (CNG) enrichment with hydrogen blend (HCNG) in counter from the conversion of the port injection gasoline engine. The intention of the investigation was to examine the performance and exhaust gases from the effect of excess air ratio and timing angle changes in consequence of hydrogen increment to natural gas in comparison to gasoline engine performance and exhaust gases as a single fuel. The compression ratio was set at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…A common observation from the previous research is that the engine efficiency improves by boosting, while NO x emission increases. Lee et al 25 had observed retarded ignition to reduce NO x slightly; similarly, Zareei and Ghadamkheir 26 had also reported a slight drop in NO x emission with retarded ignition. However, the NO x reduction was not satisfactory under minimum performance drop range.…”
Section: Introductionmentioning
confidence: 93%
“…A common observation from the previous research is that the engine efficiency improves by boosting, while NO x emission increases. Lee et al 25 had observed retarded ignition to reduce NO x slightly; similarly, Zareei and Ghadamkheir 26 had also reported a slight drop in NO x emission with retarded ignition. However, the NO x reduction was not satisfactory under minimum performance drop range.…”
Section: Introductionmentioning
confidence: 93%